1997
DOI: 10.1093/jn/127.3.514s
|View full text |Cite
|
Sign up to set email alerts
|

Trans (Elaidic) Fatty Acids Adversely Affect the Lipoprotein Profile Relative to Specific Saturated Fatty Acids in Humans

Abstract: Although dietary trans fatty acids can affect plasma lipoproteins negatively in humans, no direct comparison with specific saturated fatty acids has been reported, even though trans fatty acids were designed to replace saturates in foods and food processing. In this study, dietary trans 18:1 [elaidic acid at 5.5% energy (en)] was specifically exchanged for cis 18:1, 16:0 or 12:0 + 14:0 in 27 male and female subjects consuming moderate fat (31% en), low cholesterol (<225 mg/d) whole food diets during 4-wk diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
2
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 22 publications
4
90
2
4
Order By: Relevance
“…Several studies have shown that TFA increase lowdensity lipoprotein (LDL-C) and decrease high-density lipoprotein cholesterol (HDL-C) in humans compared with oleic acid (Judd et al, 1994;Sundram et al, 1997;Lichtenstein, 2000) with the effect of TFA on LDL-C being similar to that of butterfat (Almendingen et al, 1995). Lipoprotein(a) (Lp(a)), an independent risk factor for cardiovascular disease (CVD), was also signi®cantly higher in diets enriched with TFA compared with oleic acid or a saturated fatty acids (SFA) diet (Nestel et al, 1992;Katan et al, 1995;Aro et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that TFA increase lowdensity lipoprotein (LDL-C) and decrease high-density lipoprotein cholesterol (HDL-C) in humans compared with oleic acid (Judd et al, 1994;Sundram et al, 1997;Lichtenstein, 2000) with the effect of TFA on LDL-C being similar to that of butterfat (Almendingen et al, 1995). Lipoprotein(a) (Lp(a)), an independent risk factor for cardiovascular disease (CVD), was also signi®cantly higher in diets enriched with TFA compared with oleic acid or a saturated fatty acids (SFA) diet (Nestel et al, 1992;Katan et al, 1995;Aro et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Há algumas evidências de que modesta ingestão de ácidos graxos trans pode afetar o perfil das lipoproteínas, aumentando a lipoproteína de baixa densidade (LDL), diminuindo a lipoproteína de alta densidade (HDL) e aumentando a lipoproteína a (Lpa). No entanto, estas observações têm sido discutidas, procurando avaliar se os ácidos graxos trans são melhores ou piores do que os ácidos graxos saturados, quando utilizados na produção de alguns alimentos fritos, gorduras e margarinas [1,6,15].…”
Section: Discussionunclassified
“…A comparative study in young Australian adults showed that the total blood cholesterol, triglycerides and HDL-cholesterol levels of those fed on palm oil (palm olein) and olive oil were lower than those fed on the usual Australian diet (Choudhury et al, 1995). A double-blind cross-over study (Sundram, 1997) showed that a palm olein rich oil diet is identical to an oleic-acid rich diet.…”
Section: Mechanism Of Action Of Red Palm Oil In Improving the Immune mentioning
confidence: 99%